KINERJA REKSADANA SYARIAH TAHUN 2009DI INDONESIA - Hariandy Hasbi (University of Merdeka Malang, 2010)
Syaria mutual fund was one of the investments in capital market products thatused Islamic principle. Current ly, people started switching to this investment product thatwas felt to give a bet ter alternat ive than banking products. The purpose of this research wasto f ind out the comparison between each performance of sharia mutual funds (f ixed, stock,mixed and protect ion) and Jakarta Islamic Index(JII) as a benchmark of syaria port folio inIndonesia period 2009 using Risk Adjusted Returns Measurement (Sharpe, Treynor, and Jensen),and its prospect ive in 2010. The method of this research used purposive sampling and SPSSver.13.0 as a tools of comparat ive stat ist ical tests. Overall, these empirical results were concludedthat the performance of syaria mutual funds was viewed f rom the aspect of returnand risk variables showed a good performance compared to its market index (JII) in 2009.